Social Responsibility in the ‘Sunny Side of Life’: An exploration of CSR in the Exclusive Resort islands of the Republic of Maldives - Ahmed, Aashiyath (2009)
To date, limited research has been undertaken on the aspect of Corporate Social Responsibility (CSR) in Tourism Industry. Most of these studies have been conducted on the tour operators and hotels. In addition, the few researches that were undertaken on the resort islands revolve around the subject of sustainability and environment. Hence, there is a need to further explore the CSR in resort islands. Tourism is the most crucial economic sectors of the island states of Maldives. Among the several tourist establishments across the country, the resort islands operate comparatively on a larger scale and it has become an ideal destination for tourists around the globe. As to the date of this study, no research has been initiated to examine the CSR of tourism in Maldives and as such this is one of the first research papers looking at the subject. The purpose of this research paper is to explore the CSR status in the exclusive resort islands of Maldives. The management of the resort islands was surveyed using questionnaires to analyze their level of awareness of CSR, the level of CSR practices implemented as well as the Reporting level of CSR. In order to further validate the survey results, the stakeholders of the tourism industry were interviewed to inquire on their perception towards CSR in these resort islands. The study revealed that despite the high level of awareness on the CSR, the resort islands are lacking behind in implementing CSR practices. Moreover, majority of the resorts have not initiated CSR reporting both in their annual reports and websites. The study only focuses on the resort islands and the results of the study do not provide a complete picture of the CSR status of the entire Maldivian tourism Industry. Hence, further research is needed to determine CSR practices in other tourist establishments, tour operators and tourism related companies to determine the overall CSR in the Tourism Industry of Maldives.